Peróxido de hidrogênio no controle in situ do fitoplâncton do Açude Gavião - Ceará - Guedes, Dayvson de Oliveira (2020)
Cyanobacterial blooms in reservoirs intended for human supply cause concern for their potential to produce secondary metabolites and the risks associated with the health of mammals and aquatic communities. The removal of these microorganisms and metabolites in conventional water treatment plants is not efficient, which makes it essential to investigate alternative treatment techniques. These techniques should have quick and short-term action to quickly suppress cyanobacterial blooms, preferably without negative effects on the rest of the biota and on the overall quality of the water. In this context, hydrogen peroxide (H2O2) appears as an alternative oxidant for the control of cyanobacteria in the environment due to its selectivity and not the formation of disinfection by-products. To evaluate the effect of H2O2 in the control of cyanobacteria, the present study performed in situ experiments on a pilot scale (mesocosms) in the Gavião reservoir, used to supply part of the Metropolitan Region of Fortaleza-Ceará. A concentration of 10 mg L-1 H2O2 was applied in mesocosms installed in the reservoir and the water quality was monitored for 120 hours. The results indicate an improvement in physical parameters (Color and Turbidity) and selective suppression in phytoplankton with greater reduction in the concentration of cyanobacterial chlorophyll (from 35 μg L-1 to 4.75 μg L-1). At the end of the experiment, the chlorophyll concentration of green algae was approximately 5 times higher than the chlorophyll concentration of cyanobacteria, indicating a succession of the phytoplanktonic community, initially dominated by cyanobacteria, to a community dominated by green algae. From the PCA analysis, it was found that cyanobacteria were controlling the process of generating O2 and CO2 consumption. Although some studies have shown the effectiveness of H2O2 treatment in water used for recreation, the results have shown that relatively low concentrations can be used not only for the selective elimination of cyanobacteria but also for improving water quality.